2003
DOI: 10.4049/jimmunol.171.9.4650
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Organization and Expression Analysis of B7-H4, an Immune Inhibitory Molecule of the B7 Family

Abstract: B7-H4 is a recently identified B7 family member that negatively regulates T cell immunity by the inhibition of T cell proliferation, cytokine production, and cell cycle progression. In this study, we report that the genomic DNA of human B7-H4 is mapped on chromosome 1 comprised of six exons and five introns spanning 66 kb, of which exon 6 is used for alternative splicing to generate two different transcripts. Similar B7-H4 structure is also found in mouse genomic DNA in chromosome 3. A human B7-H4 pseudogene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
231
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(243 citation statements)
references
References 18 publications
10
231
1
Order By: Relevance
“…Recent reports, however, indicate focal and infrequent protein expression in certain somatic tissues, including distal convoluted tubules of the kidney, ductal and acinar cells of the pancreas, endometrial glands, transitional epithelia of the ureter and bladder, bronchial epithelium of the lung, and columnar epithelium of the gallbladder (5). Additionally, B7-H4 has been found to be aberrantly expressed at high levels in human serous, endometrioid, and clear cell ovarian carcinoma; ductal and lobular breast cancer; and lung cancer (5,6,21). This overexpression of B7-H4 by malignant tissues may render B7-H4 a particularly useful target for facilitating antitumoral immunotherapeutic responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports, however, indicate focal and infrequent protein expression in certain somatic tissues, including distal convoluted tubules of the kidney, ductal and acinar cells of the pancreas, endometrial glands, transitional epithelia of the ureter and bladder, bronchial epithelium of the lung, and columnar epithelium of the gallbladder (5). Additionally, B7-H4 has been found to be aberrantly expressed at high levels in human serous, endometrioid, and clear cell ovarian carcinoma; ductal and lobular breast cancer; and lung cancer (5,6,21). This overexpression of B7-H4 by malignant tissues may render B7-H4 a particularly useful target for facilitating antitumoral immunotherapeutic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Although B7-H4 mRNA has been noted in a number of nonlymphoid organs (3), it was originally believed that protein expression was restricted to activated lymphoid cells (4,6,7). Recent reports, however, indicate focal and infrequent protein expression in certain somatic tissues, including distal convoluted tubules of the kidney, ductal and acinar cells of the pancreas, endometrial glands, transitional epithelia of the ureter and bladder, bronchial epithelium of the lung, and columnar epithelium of the gallbladder (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, B7x protein expression seems to be more restricted compared with B7-H3. Despite mRNA expression in various human tissues, immunohistochemistry (IHC) for B7x fails to reveal detectable protein expression in any healthy human organs (23). In stark contrast, aberrant expression of B7x has been observed in cancers of the breast (22,24), lung (16), ovary (22,25), uterus (26), and kidney (27).…”
mentioning
confidence: 99%
“…The same study showed that B7-H4-Fc proteins suppressed the expansion of bone marrow-derived CD11b + Gr-1 + neutrophil progenitors in vitro. Apart from the immune system, B7-H4 transcripts and proteins are overexpressed in breast cancer (11)(12)(13), ovarian cancer (6,(13)(14)(15)(16), lung cancer (6,17,18), and many other solid tumors (19)(20)(21)(22)(23)(24)(25) to varying extents. In some cancers, the proportion of B7-H4-positive tumor area and the intensity of B7-H4 immunostaining have been positively correlated with the invasiveness of the tumors, poor prognosis, and mortality (20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%